CloudTran++: Improved Cloud Removal from Multi-Temporal Satellite Images Using Axial Transformer Networks - Dionysis Christopoulos; Valsamis Ntouskos; Konstantinos Karantzalos (Remote Sensing)
We present a method for cloud removal from satellite images using axial transformer networks. The method considers a set of multi-temporal images in a given region of interest, together with the corresponding cloud masks, and produces a cloud-free image for a specific day of the year. We propose the combination of an encoder-decoder model employing axial attention layers for the estimation of the low-resolution cloud-free image, together with a fully parallel upsampler that reconstructs the image at full resolution. The method is compared with various baselines and state-of-the-art methods on Sentinel-2 datasets of different coverage, showing significant improvements across multiple standard metrics used for image quality assessment.